Hyperchloraemic metabolic acidosis following open cardiac surgery. Issue 12 (13th September 2005) - Hatherill, M; Salie, S; Waggie, Z; Lawrenson, J; Hewitson, J; Reynolds, L; Argent, A
Abstract : Aims: To describe acid–base derangements in children following open cardiac surgery on cardiopulmonary bypass (CPB), using the Fencl–Stewart strong ion approach. Methods: Prospective observational study set in the paediatric intensive care unit (PICU) of a university children's hospital. Arterial blood gas parameters, serum electrolytes, strong ion difference, strong ion gap (SIG), and partitioned base excess (BE) were measured and calculated on admission to PICU. Results: A total of 97 children, median age 57 months (range 0.03–166), median weight 14 kg (range 2.1–50), were studied. Median CPB time was 80 minutes (range 17–232). Predicted mortality was 2% and there was a single non-survivor. These children showed mild metabolic acidosis (median standard bicarbonate 20.1 mmol/l, BE −5.1 mEq/l) characterised by hyperchloraemia (median corrected Cl 113 mmol/l), and hypoalbuminaemia (median albumin 30 g/l), but no significant excess unmeasured anions or cations (median SIG 0.7 mEq/l). The major determinants of the net BE were the chloride and albumin components (chloride effect −4.8 mEq/l, albumin effect +3.4 mEq/l). Metabolic acidosis occurred in 72 children (74%) but was not associated with increased morbidity. Hyperchloraemia was a causative factor in 53 children (74%) with metabolic acidosis. Three (4%) hyperchloraemic children required adrenaline for inotropic support, compared to eight children (28%) without hyperchloraemia. Hypoalbuminaemia was associated with longer duration of inotropic support and PICU stay. Conclusions: In these children with low mortality following open cardiac surgery, hypoalbuminaemia and hyperchloraemia were the predominant acid–base abnormalities. Hyperchloraemia was associated with reduced requirement for adrenaline therapy. It is suggested that hyperchloraemic metabolic acidosis is a benign phenomenon that should not prompt escalation of haemodynamic support. By contrast, hypoalbuminaemia, an alkalinising force, was associated with prolonged requirement for intensive care.